(untitled) (American International Journal of Biology and Life Sciences, 2021)
In 2014 we have isolated and cloned the sea star Igkappa gene which induced an anti-HRP primitive invertebrate antibody. We attempt, in the present work, to produce a SIP Young 6 His protein through HeK 293 EBNA cells after Igkappa gene cloning. This protein bound HRP by the use of Escherichia coli as vector of cloning but not HRP with HeK cells as vector. Is there changes in sea star IGKappa gene expression? We notice also that the SARS-CoV-2-SPIKE RBD Protein didn’t bind to SIP Young 6 His protein when compared to HRP.